2017
DOI: 10.3390/nu9040416
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Ankle Brachial Index, Protein-Energy Wasting, and Inflammation Status with Cardiovascular Mortality in Patients on Chronic Hemodialysis

Abstract: Protein-energy wasting (PEW) is highly prevalent in hemodialysis (HD) patients. We investigated the association of abnormal ankle brachial index (ABI), PEW, and chronic inflammation status with clinical prognosis in HD patients. A total of 973 HD patients were enrolled and were followed-up for 8 years. As a marker of the PEW, geriatric nutritional risk index (GNRI) was used. Cut-off levels were 91.2 for GNRI defined from previous studies and 1.9 mg/L for C-reactive protein (CRP) as median value, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Moreover, the author further analyzed the cutoff value of CRP and nutrition status index and showed that both GNRI under 91.2 and CRP over 1.9 mg/L independently predicted mortality due to CVD, respectively. Furthermore, the combination of these variables increases their predictive values for the risk of mortality due to CVD and allcause mortality in HD patients [31]. Lee et al revealed that a worsening or stationary GNRI was independently associated with higher risk for major adverse cardiac and cerebrovascular events (MACCEs) in PD patients by multivariate cox analysis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the author further analyzed the cutoff value of CRP and nutrition status index and showed that both GNRI under 91.2 and CRP over 1.9 mg/L independently predicted mortality due to CVD, respectively. Furthermore, the combination of these variables increases their predictive values for the risk of mortality due to CVD and allcause mortality in HD patients [31]. Lee et al revealed that a worsening or stationary GNRI was independently associated with higher risk for major adverse cardiac and cerebrovascular events (MACCEs) in PD patients by multivariate cox analysis [48].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The Geriatric Nutritional Risk Index (GNRI) was proposed by Bouillanne et al to evaluate nutritional disorders in older adults. [5][6][7][8][9][10] Sarcopenia is defined as an age-related involuntary loss of skeletal muscle mass and strength, and it results in physical disability, a poor quality of life and increased risk of death. [5][6][7][8][9][10] Sarcopenia is defined as an age-related involuntary loss of skeletal muscle mass and strength, and it results in physical disability, a poor quality of life and increased risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…4 In recent years, the GNRI has been used to evaluate the nutritional condition of older adults, and an association between the GNRI and prognosis has been reported. [5][6][7][8][9][10] Sarcopenia is defined as an age-related involuntary loss of skeletal muscle mass and strength, and it results in physical disability, a poor quality of life and increased risk of death. 11,12 However, few studies have focused on the relationship between the GNRI and sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transfemoral intervention, which is a known predictor of bleeding complications after PCI, was performed more frequently in dialysis patients than in nondialysis patients mainly because of the presence of an arteriovenous shunt in the upper extremity. In addition to conventional risk factors for CAD, several CKD‐related factors such as chronic inflammation, renal anemia, oxidative stress, and protein‐energy wasting may also be associated with advanced atherosclerosis and poor outcomes after PCI in dialysis patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition to conventional risk factors for CAD, several CKDrelated factors such as chronic inflammation, renal anemia, oxidative stress, and protein-energy wasting may also be associated with advanced atherosclerosis and poor outcomes after PCI in dialysis patients. 1,8,15,26,27 Importantly, despite the increased risk for adverse outcomes, dialysis patients are less likely to receive guideline-recommended medical therapy and invasive procedures including PCI and CABG compared with nondialysis patients. 11,15 Physicians should recognize that the prevalence of severe CAD in dialysis patients is high, and treat these patients appropriately with both noninvasive and invasive methods including optimal medical therapy, diet therapy, cardiac rehabilitation, counseling for lifestyle improvements, PCI and CABG.…”
Section: Discussionmentioning
confidence: 99%